التنافس الإيراني التركي على منطقة الشرق الأوسط 2016 -200 - قويدر, خالد (جامعة الوادي University of Eloued, 2017)
تسعى الدراسة إلى إبراز الأهمية الإستراتجية لمنطقة الشرق الأوسط التي تضم إلى جانب العالم العربي كلا من تركیا وٕإيران، والتي تعتبر ساحة تنافس وصراع بین أكثر من طرف إقلیمي لبسط النفوذ والسیطرة علیها، هذه المنطقة ذات الموقع الإستراتیجي الهام والإرث الحضاري المتمیز تعرضت لجملة من التحولات السیاسیة، التي أدت إلى إنهيار مرتكزات النظام الإقلیمي العربي وخلفت فراغا إستراتیجيا في المنطقة، ما أدى إلى تنافس القوى الإقلیمیة لملء هذا الفراغ، بحیث ظهرت إيران وتركیا كقوتین إقلیمیتین بارزتين تسعى كل منهما لفرض مشروع إقلیمي طموح ، وذلك بالتمدد في المنطقة لكي يكون لها دورا كقوة إقليمية مؤثر في السياسة العالمية، وبالتالي من المتوقع أن یؤدي ذلك إلى حدوث تنافس كبیر بینهما في الكثیر من القضایا والملفات الإقلیمیة، وهذا ما ینعكس سلبا على المنطقة وعلى الأمن القومي العربي، ومنه يعتبر بأن مستقبل المنطقة مرهون بمستقبل التنافس بین هذین القوتین في ظل غياب قوة إقلیمیة عربیة The study seeks to highlight the importance strategy for the middle East, which includes me along the Arab world both of Turkey, Iran, which is a square compete conflict between more than a party a regional extend of power and control, this area with a strategic location important and inheritance of civilization outstanding been a lot of shifts political whith led to the collapse of the acquired regional arab system and created a vacuum strategically in the region, leading to compete powers regional to fill the void, so that appeared Iran and Turkey emerges as a prominent regional powers seeking to impose ambitious regional projects by expanding the region in order to have a role as a regional influential in the world politics, and therefore is expected to lead to a competition large between them in many cases, files, regional, this is reflected negatively area on the Arab National security, and from consider that the future of the area is subject to the future of competition between these two forces in the absence of the power of regional Arab.
أنظمة مقارنة وحكم راشد
Keywords: الصراع ،التنافس ،الدور الاقليمي ،القوة الاقليمية ،النفوذ .; Conflict, competition, regional role, regional power, influence